On population structure and marriage dynamics - Eugenio P. Giolito (Institute for the Study of Labor (IZA), 2010)
I develop an equilibrium, two-sided search model of marriage with endogenous population growth to study the interaction between fertility, the age structure of the population and the age at first marriage of men and women. Within a simple two-period overlapping generation model I show that, given an increase of the desired number of children, age at marriage is affected through two different channels. First, as population growth increases, the age structure of the population produces a thicker market for young people, inducing early marriages. The second channel comes from differential fecundity: if the desired number of children is not feasible for older women, women tend to marry younger and men older, with single men outnumbering single women in equilibrium. Using an extended version of the model to a finite number of periods and fertility data, I show that two mechanisms described above may have acted as persistence mechanisms after the US baby boom. I show that demographic transitional dynamics after the baby boom may account for approximately a 23% of the increase in men's age of marriage between 1985 and 2009, albeit the impact on women's age is small.
Keywords: J12; D83; 330; marriage; population structure; search; Ehe; Altersstruktur der Bevölkerung; Familienökonomik; Schätzung; USA